Biophysical and molecular mechanisms of ESCRT functions, and their implications for disease. (April 2022) - Migliano, Simona Maria; Wenzel, Eva Maria; Stenmark, Harald
Abstract: The endosomal sorting complex required for transport (ESCRT) machinery evolved early in evolution to sculpt and cut cellular membranes. Consisting of three subcomplexes termed ESCRT-I, -II and -III, this machinery is recruited to various cellular locations to perform key steps in essential processes such as protein degradation, cell division, and membrane sealing. Here we review recent discoveries that have shed light on biophysical and molecular mechanisms of ESCRTs in endolysosomal protein degradation and nuclear envelope sealing, and we discuss how dysfunctional ESCRTs can lead to diseases such as cancer and neurodegenerative disorders.